2014
DOI: 10.1159/000357370
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Quality and Outcomes Framework: Quality Indicators for Diabetes Management in Swiss Primary Care Based on Electronic Medical Records

Abstract: Background: Most industrialized countries are faced with a growing population of patients with chronic diseases and multimorbidity. Evidence performance gaps have been recognized in the treatment of this vulnerable patient group. In England, the Quality and Outcomes Framework (QOF) - based on incentivized quality indicators - has been established to narrow the gap. Objective: We evaluated to what extent clinical data, extracted from electronic medical records (EMRs) of Swiss general practitioners, can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…In fact, the prevalence of patients with diabetes was approximately 15 % in our study population and therefore in the expected range considering age and morbidity [ 14 ]. Moreover, previous studies have shown that the majority of patients with diabetes in Swiss primary care undergo regular BP measurement [ 15 ]. Apparently, GPs are aware of the necessity of BP control in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the prevalence of patients with diabetes was approximately 15 % in our study population and therefore in the expected range considering age and morbidity [ 14 ]. Moreover, previous studies have shown that the majority of patients with diabetes in Swiss primary care undergo regular BP measurement [ 15 ]. Apparently, GPs are aware of the necessity of BP control in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…One example of an unsuccessful introduction of computerised information systems in Thailand is the abandoned Telemedicine Network launched in 1998; it failed because of the lack of IT skills among health professionals, the low level of system acceptance among users, and the rapid changes in the IT system 12, 13 . In addition, a study on the QOF in Switzerland 14 revealed that an incomplete database was unable to reflect the quality of healthcare delivery. Furthermore, different studies suggest that healthcare workers should be able to perform proper data entry, and these data should be used as feedback for improving the quality of healthcare delivery [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on the QOF in Switzerland 14 revealed that an incomplete database was unable to reflect the quality of healthcare delivery. Furthermore, different studies suggest that healthcare workers should be able to perform proper data entry, and these data should be used as feedback for improving the quality of healthcare delivery [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Using diabetes type 1 and 2 as an exemplary chronic illness condition, Djalali et al [[7], this issue] introduce a feasibility study on the development of a novel quality and outcomes framework for Switzerland (SQOF) compared to a similar framework implemented in Great Britain. The SQOF is based on available electronic medical records from general practitioners and aims at narrowing the evidence-performance gap identified in clinical settings for vulnerable patients such as those suffering from multiple chronic conditions.…”
Section: Brief Overview Of the Special Section Issue Contributionsmentioning
confidence: 99%